Energy metabolism as possible stimulus of growth hormone response to high intensity exercise - Bernardi, M.; Rosponi, A.; Cama, E.; Egidi, F.; Ballesio, M.; Faiola, F.; Lenzi, A.; Radicioni, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Mechanisms regulating growth hormone (GH) release after exercise in humans are not fully understood (Stokes, 2003). Among these mechanisms, factors that stimulate lactic anaerobic metabolism and/or the ratio of oxygen demand to oxygen availability are supposed to provide a regulatory signal for GH response to continuous aerobic and intermittent exercise (VanHelder, 1984; VanHelder, 1987). The present study is aimed at evaluating the hypothesis that GH response to an upper body short duration high intensity exercise is also influenced by the same energy sources. Sixteen male subjects underwent an arm cranking ergometer -ACE- (ER800, Cosmed, Italy) maximal incremental exercise test to assess intensity for a 150% oxygen uptake peak constant power anaerobic exercise test (AnT). The AnT was carried out with the same ACE and performed up to exhaustion under metabolic and cardiac monitoring (Quark b2, Cosmed, I; LactatePro, ARKRAI, Japan). Venous blood samples were collected before and after the AnT to assess GH concentration (IRMA, Abbott Laboratories, Abbott Park Illinois, USA). Blood Lactate (BL) and oxygen uptake during and after (fast and slow excess of oxygen consumption -EPOC) the AnT were analyzed to estimate the energy expenditure (EE) contribution to perform the exercise (di Prampero PE, 1981; Beneke et al., 2002). After the exercise GH showed a relevant increment (113±91 times higher than basal values) with peak values equal to 7.1±3.55 ng/ml (at the 27±11minute of recovery) and total production of 408±230 ng/ml. AnT total EE was equal to 139±36.7 kJ. BL peak (12±2 mmol/l at the sixth minute of recovery and whose EE contribution corresponded to 56.6±14.4 kJ) did not show any correlation with GH increase. Significant correlations were found between GH increment and both anaerobic alactic metabolism (EE=34.4±12.7 kJ) and aerobic metabolism (EE=48.5±17.1kJ) with r equal to 0.6 and -0.54, respectively. The ratio between alactic-anaerobic/aerobic EE was positively correlated with the GH increment (r=0.66). The present study in upper body AnT confirms the results of the authors who found in sub-maximal lower body exercises a positive correlation between GH peak and oxygen deficit (Lassarre et al., 1974) and in both acute hypoxic and altitude exercise a faster and greater GH response than at sea level (Raynolds et al., 1981). In conclusion, this study indicates the use of high energy phosphates and an insufficient oxygen supply as possible stimuli for GH increment after exercise.